Effect of intermittent and continuous caloric restriction on Sirtuin1 concentration depends on sex and body mass index - Opstad, Trine B.; Sundfør, Tine; Tonstad, Serena; Seljeflot, Ingebjørg (Nutrition, metabolism, and cardiovascular diseases, 2021)
The favorable effect of caloric restriction (CR) on health span is well known and partly mediated by the sirtuin system. Sirtuin1, a regulator of energy homeostasis in response to nutrient availability, is activated by CR. We therefore investigated effects of two different CR regimens on Sirtuin1 concentrations. The study included 112 abdominally obese subjects, randomized to intermittent or continuous CR for 1 year. Blood samples and anthropometric measures were collected at baseline and after 12 months. Sirtuin1 concentrations were measured by ELISA. Sirtuin1 correlated significantly to BMI at baseline (r = .232, p = 0.019). Mean reduction in body-weight was 8.0 and 9.0 kg after intermittent and continuous CR, respectively. After 1 year, no significant between-group differences in Sirtuin1 levels were observed according to regimen (p = 0.98) and sex (p = 0.41). An increase in median Sirtuin1 concentrations (pg/mL) [25, 75 percentiles] from baseline was observed after intermittent CR in the total population (884 [624, 1285] vs.762 [530, 1135]; p = 0.041), most marked in men (820 [623, 1250] vs. 633 [524, 926]; p = 0.016). Improvement in BMI after 1 year correlated to Sirtuin1 changes, but varied according to sex. In women, Spearman's rho = .298, p = 0.034, with stronger correlation in the intermittent CR group (r = .424, p = 0.049). In men, there was an inverse relation to Sirtuin1 changes, only in the intermittent CR group (r = −.396, p = 0.045). Effects on Sirtuin1 concentrations after 1 year of CR are sex and BMI-related. Intermittent CR regimen affected Sirtuin1 to a stronger extent than continuous CR, suggesting individualized dietary intervention. [Display omitted] •Continuous and intermittent caloric restriction did not affect SIRT1 differently.•SIRT1 increased after intermittent caloric restriction, especially in men.•Reduced BMI after caloric restriction may drive sex-related SIRT1 changes.